Safety orientation - Dukatsch, J.W.; The MARCOM Group, Ltd. (Boothwyn, PA : The MARCOM Group, Ltd., 2007)
The program comprises the information abaout mental preparation, safety housekeeping and accident prevention, personal protective equipment, safe work practices and preparing for emergencies
Title from title screen
Executive producer, Den Leonard ; editor, J.W. Dukatsch
Narrator: Don Dawson
Keywords: Industrial safety; Safety education, Industrial